Selection of popcorn genotypes resistant to Spodoptera frugiperda and identification of resistance-related key traits - Amanda Tami Kuroda; Jocimar Costa Rosa; André Luís Hartmann Caranhato; Luiz Felipe Antunes de Almeida; Giovana Dal Lago Garcia; Gustavo Arana Demitto; Renata Maria Bento de Souza; Fernando Alves de Albuquerque (Acta Scientiarum. Agronomy, 2023)
The Spodoptera frugiperda, is one of the most deleterious pests of popcorn and the identification of resistant genotypes is determinant in breeding programs. The objective of this study was to select popcorn genotypes resistant to S. frugiperda and the key traits related to the identification of resistance. The popcorn varieties UEM J1, Composto Márcia, Arachida, Composto Gaúcho, and Zapalote Chico (resistant check) were evaluated in a completely randomized design with 100 replications. The experimental unit consisted of one Petri dish, containing plant material and a caterpillar The following traits were evaluated: larval stage duration (LSt), food intake weight(IW), final larva weight (FW), mean larva weight (MW), feces (F), assimilated (A) and metabolized food weight (M), relative consumption rate (RCR), relative metabolic rate (RMR), relative growth rate (RGR), conversion efficiency of ingested food (CEI), apparent digestibility (AD), conversion efficiency of digested food (CED), and leaf area consumed (LAC). The diagnosis of multicollinearity, analysis of canonical variables, genetic divergence, hierarchical clustering, factor analysis and canonical correspondence analysis were carried out to perform multivariate analysis. After the multicollinearity test, the traits FW, IW, RCR, AD, and LAC were maintained for further analysis. The traits IW, FW and AD were determinant in the resistance by antixenosis expressed by the varieties Zapalote Chico and Arachida, for the varieties Composto Gaúcho and Composto Márcia the determining characteristics were RCR and LAC and for the variety UEM J1 the variable LAC showed greater importance. Variety Arachida was considered resistant to S. frugiperda by antixenosis and can be used in the future as a source of favorable alleles to breed resistant popcorn hybrids. The traits relative consumption rate, apparent digestibility and leaf area consumed were considered key traits in the identification of resistance against S. frugiperda in popcorn genotypes.